(untitled) (Glocalism: Journal of Culture, Politics and Innovation, 2020)
Food is an effective symbol capable of strongly evoking a cultural identity. In the case of Sicily, this role is mainly played by pastry, and in particular by two sweets: cannolo (the singular of cannoli) and cassata. But how does it happen that just these two preparations, rather than others, take on this value? What are their meanings and what determines them? Are cannolo and cassata the expression of a remote and spontaneous tradition as we generally like to believe? Semiotic analysis not only leads us to understand the complexity of these two pieces of a gastronomy, but also to reflect on the whole notion of symbol, rethinking its limits and possibilities.